Exploring Trait Emotional Intelligent: Survey on Students during Covid-19 - Muhamad Deni Johansyah; Iwan Sidharta (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
The Covid-19 pandemic period caused changes in student behavior in teaching and learning caused by stressors. To overcome the impact of stress caused by the Covid-19 pandemic, it is necessary first to know the level of intellectual emotionality. This study explores the Emotional Intelligent Trait measurement during the Covid-19 pandemic from a student's point of view. One hundred twenty-two valid survey instruments were collected using online media. The research instrument adopted from TEIQue SF as many as 30 statement instruments. Processing data analysis uses a factor analysis approach to know how many factors make up the Emotional Intelligent Trait measurement. Two factors make up Trait Emotional Intelligent with nine statement items. The study results can use as a reference for measuring Trait Emotional Intelligent to manage student emotions in the teaching and learning process.